Synthesis of 2-(Chlorodifluoromethyl)indoles for Nucleophilic Halogen Exchange with [18F]Fluoride - Bock, Leonard; Schultheiss, Stefanie K.; Maschauer, Simone; Lasch, Roman; Gradl, Susanne; Prante, Olaf; Zard, Samir Z.; Heinrich, Markus (European Journal of Organic Chemistry, 2021)
The synthesis of 2-[18F]trifluoromethylated indoles from the corresponding chlorodifluoromethyl precursors was found to proceed under milder conditions when compared to known metal-free nucleophilic exchange reactions with [18F]fluoride on chlorodifluoro-methyl arenes. A key element in the reaction course is – most likely – a favorable elimination-addition mechanism on the 2-methyl position of the indole. Given the increasing interest in 18F-labelled compounds, this single step labeling methodology nicely complements the so far existing routes to 2-[18F]trifluoromethylated indoles.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Fluorine; Indoles; Nucleophilic substitution; Radical reactions; Radiochemistry